2020
DOI: 10.1111/1755-0998.13209
|View full text |Cite
|
Sign up to set email alerts
|

Genomic basis of environmental adaptation in the leathery sea squirt (Styela clava)

Abstract: Tunicates occupy the evolutionary position at the boundary of invertebrates and vertebrates. It exhibits adaptation to broad environmental conditions and is distributed globally. Despite hundreds of years of embryogenesis studies, the genetic basis of the invasive habits of ascidians remains largely unknown. The leathery sea squirt, Styela clava, is an important invasive species. We used the chromosomal‐level genome and transcriptome of S. clava to explore its genomic‐ and molecular‐network‐based mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 95 publications
0
36
0
Order By: Relevance
“…A total of 17,428 protein-coding genes were identified, 15,734 of which were annotated in the S. clava genome [ 28 ]. Based on our previous study, we further identified 553 TF genes, which were distributed in 60 TF families in the S. clava genome, according to the domain annotation of proteins and the types of DBD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 17,428 protein-coding genes were identified, 15,734 of which were annotated in the S. clava genome [ 28 ]. Based on our previous study, we further identified 553 TF genes, which were distributed in 60 TF families in the S. clava genome, according to the domain annotation of proteins and the types of DBD.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the expression profiles of TFs during the development of S. clava , we acquired the fragments Per Kilobase of gene per million mapped reads (FPKM) value of each TF in 2-cell–8-cell embryos (2–8 cells), gastrula embryos (gast), neurula embryos (neu), tailbud-stage embryos (tb), hatched swimming larvae (hsl), tail-regressed larvae (trl), and metamorphic juveniles (mj) by RNA-sequencing [ 28 ]. These data were further validated through quantitative real-time PCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural selection in genomes of several marine animals, such as oyster and scallop, could play a role of molecular adaptation to marine environment [5,6]. Recently, the genome of leathery sea squirt (Styela clava) has also been sequenced and analyzed for the understanding of their environmental adaptation [7]. However, the genetic basis driving ascidians to contribute and adapt marine ecosystem remains to be elusive.…”
Section: Introductionmentioning
confidence: 99%